Dialogue on Tipaimukh Dam - Dialogue on Dams & Development: the Case of Tipaimukh Dam (2010 : Muolhlum, India); Dena, Lal, 1943- (New Delhi : Akansha Pub. House, 2011)
Papers presented at the seminar held at Muolhlum, Manipur, 13-15 Dec., 2010.
Includes bibliographical references and index.
Maisha
Keywords: Dam safety -- India -- Tipaimukh -- Congresses; Dams -- Environmental aspects -- India -- Tipaimukh -- Congresses; Dams -- Social aspects -- India -- Tipaimukh -- Congresses